Value of apparent diffusion coefficient for predicting malignancy of intraductal papillary mucinous neoplasms of the pancreas - Lei Zhang; Sheng-Xiang Rao; Xue-Feng Xu; Dan-Song Wang; Da-Yong Jin; Meng-Su Zeng (Diagnostic and Interventional Radiology, 2016)

(untitled)
PURPOSE: We aimed to explore the potential value of the whole tumor apparent diffusion coefficient (ADC) for discriminating between benign and malignant intraductal papillary mucinous neoplasms (IPMNs) of the pancreas.METHODS:Forty-two patients underwent 1.5 T magnetic resonance imaging that included diffusion-weighted imaging (DWI, b=0.500 s/mm2). The mean, minimum, and maximum ADC values were measured for the whole tumor. The differences between benign and malignant IPMNs were calculated for the mean ADC, ADC-min, and ADC-max values. Receiver operating characteristics (ROC) analysis was conducted to evaluate their potential diagnostic performance.RESULTS:Fifteen of 25 benign IPMNs demonstrated low or iso-signal intensity on DWI with a b value of 500 s/mm2 compared with normal pancreatic parenchyma, whereas all malignant IPMNs demonstrated high signal intensity. The mean value of ADC was significantly higher in benign IPMNs compared with malignant IPMNs (3.39×10−3 mm2/s vs. 2.39×10−3 mm2/s, P < 0.001), with an area under the ROC curve (AUC) of 0.92 (95% confidence interval [CI], 0.79–0.98). The ADC-min value of malignant IPMNs was also significantly lower than that of benign IPMNs (1.24×10−3 mm2/s vs. 2.58×10−3 mm2/s, P < 0.001), with an AUC of 0.94 (95% CI, 0.82–0.99). No marked difference was found between benign and malignant IPMNs for the ADC-max value (3.89×10−3 mm2/s vs. 3.78×10−3 mm2/s, P = 0.299).CONCLUSION:Lower mean and minimum ADC values of the whole tumor might be potential predictors of malignant IPMNs of the pancreas.